Autophagy Impairment in App Knock-in Alzheimer’s Model Mice - Jiang, Richeng; Shimozawa, Makoto; Mayer, Johanna; Tambaro, Simone; Kumar, Rakesh; Abelein, Axel; Winblad, Bengt; Bogdanovic, Nenad; Nilsson, Per (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is characterized by impaired protein homeostasis leading to amyloid-β peptide (Aβ) amyloidosis. Amyloid precursor protein (APP) knock-in mice exhibit robust Aβ pathology, providing possibilities to determine its effect on protein homeostasis including autophagy. Here we compared human AD postmortem brain tissue with brains from two different types of App knock-in mice, AppNL–F and AppNL–G–F mice, exhibiting AD-like pathology. In AD postmortem brains, p62 levels are increased and p62-positive staining is detected in neurons, including potential axonal beadings, as well as in the vasculature and in corpora amylacea. Interestingly, p62 is also increased in the neurons in 12-month-old AppNL–G–F mice. In brain homogenates from 12-month-old AppNL–G–F mice, both p62 and light chain 3 (LC3)-II levels are increased as compared to wildtype (WT) mice, indicating inhibited autophagy. Double immunostaining for LC3 and Aβ revealed LC3-positive puncta in hippocampus of 24-month-old AppNL–F mice around the Aβ plaques which was subsequently identified by electron microscopy imaging as an accumulation of autophagic vacuoles in dystrophic neurites around the Aβ plaques. Taken together, autophagy is impaired in App knock-in mice upon increased Aβ pathology, indicating that App knock-in mouse models provide a platform for understanding the correlation between Aβ and autophagy.